Pedagogical features of the development of sociocultural competence in the process of Rural Education - Tamozhska, Iryna; Piddubna, Nataliia; Pavlova, Inna; Iievliev, Oleksandr; Varga, Natalia (Tocantinópolis : Universidade Federal do Norte do Tocantins, 2022)
The main purpose of the study is to determine the main features of the pedagogical aspects of sociocultural competence as an element of intercultural communication. Sociocultural competence involves the inclusion of students in intercultural communication, modeled in the classroom in rural education. The implementation of intercultural communication presupposes an adequate mutual understanding of communication participants who are representatives of different cultures. The development of psychological and pedagogical theory and practice has led to increased attention to the formation of sociocultural competence of students in the process of their professional training in rural education. The methodology includes a number of theoretical and research bibliographic methods. First of all, methods of analysis and synthesis of scientific and practical information were applied. The method of systematization and abstract-logical was also applied. As a result, the key aspects of sociocultural competence were identified as an element of the psychology of intercultural communication. Further development is needed on issues related to the formation of sociocultural competence in future students and the use of interdisciplinary connections in the process of their professional training in rural education.

El objetivo principal del estudio es determinar las principales características de los aspectos pedagógicos de la competencia sociocultural como elemento de la comunicación intercultural. La competencia sociocultural implica la inclusión de los estudiantes en la comunicación intercultural, modelada en el aula de la educación rural. La implementación de la comunicación intercultural presupone una adecuada comprensión mutua de los participantes de la comunicación, que son representantes de diferentes culturas. El desarrollo de la teoría y la práctica psicológica y pedagógica ha llevado a una mayor atención a la formación de competencias socioculturales de los estudiantes en el proceso de su formación profesional en la educación rural. La metodología de investigación implicó el uso de una serie de métodos teóricos modernos que hicieron posible lograr este objetivo. Como resultado, se identificaron los aspectos clave de la competencia sociocultural como un elemento de la psicología de la comunicación intercultural. Es necesario profundizar en temas relacionados con la formación de competencias socioculturales en los futuros estudiantes y el uso de conexiones interdisciplinarias en el proceso de su formación profesional en la educación rural.
Rasgos pedagógicos del desarrollo de la competencia sociocultural en el proceso de educación rural
Accession Number WOS: 000777575500001
Keywords: SOCIAL SCIENCES; pedagogy; sociocultural competence; communication; psychology; education; pedagogía; competencia sociocultural; comunicación; psicología; educación